Vitamin D deficiency and adverse fetal outcome - Chandel, Anu B.; Sharma, Anoop; Mittal, Rita; Mittal, Shivika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Vitamin D deficiency is recognized as the most untreated nutritional deficiency in the world. It is plausible that vitamin D deficiency could make the fetal heart more vulnerable to distress/birth asphyxia. Vitamin D deficiency has been hypothesized to be associated with low birth weight, low Apgar score at birth, higher rates of still births and admission to NICU. The aim of present study was to study prevalence of vitamin D deficiency in pregnancy and evaluate perinatal outcome. Methods: The study was conducted in the department of obstetrics and gynecology, Kamla Nehru Hospital, Shimla, India over a period of 12 months. Six hundred women were included in the study. Results: All the mothers who had still births suffered from vitamin D deficiency and the severe vitamin D deficiency was there in 90.91% (30) of these subjects. Severe vitamin D deficiency was seen in 78.95% (75) of the subjects having babies with birth weights <2.5 kg compared to 61.16% (288) subjects of the other group. Conclusions: Adverse fetal outcome are more common in vitamin D deficient group.